International educators' perspectives on the purpose of science education and the relationship between school science and creativity. Issue 1 (2nd January 2020) - Hetherington, Lindsay; Chappell, Kerry; Ruck Keene, Hermione; Wren, Heather; Cukurova, Mutlu; Hathaway, Charlotte; Sotiriou, Sofoklis; Bogner, Franz
ABSTRACT: Background : Creativity is often viewed as a fundamental educational capability. Science can play a role in nurturing creativity. Research suggests that creative pedagogy, including interdisciplinary teaching, can engage students with science. Previous studies into teachers' attitudes to science and creativity have been largely situated within national educational contexts. Purpose : This study explores educators' perspectives on the relationship between Science and Creativity across national contexts drawn from Europe and beyond. Sample and Methods : A convenience sample of 270 educators, recruited by project partners and via online media, and broadly defined to include teachers, trainee teachers, informal educators and teacher educators, responded to an online survey designed to explore perceptions of the relationship between science and creativity. Exploratory factor analysis of Likert question responses was used to develop a combined attitude scale, with results compared across nationalities and phases of education. Open question responses were analysed thematically to allow nuanced interpretation of the descriptive statistical findings. Results : The findings show broad agreement internationally that science is a creative endeavour, with a small number of educators disagreeing about the relationship between science and creativity in the context of school science. Those who disagreed were usually secondary science teachers, from England, Malta or outside Europe (primarily from the United States). The role of scientific knowledge within creativity in science education was found to be contentious. Conclusions : That educators broadly see science as creative is unsurprising, but initial exploration of educators' perspectives internationally reveals some differences, particularly amongst educators working in formal education, relating to the role of knowledge with respect to creativity in science. With current interest in STEAM education, further investigation to understand potential mediating factors of national educational contexts on teachers' perspectives with respect to the role of disciplinary knowledge(s) in creativity and their interaction in interdisciplinary teaching and learning, is recommended.